THE DEVELOPMENT OF TOURIST ATTRACTIONS, FACILITIES AND QUALITY OF SERVICE TO VISITOR SATISFACTION IN RAGUNAN WILDLIFE PARK - Tiara Dita Puspita; Dimas Putra) Dedityatama (Sekolah Tinggi Pariwisata Mataram, 2022)
This research is supported by the high tourism growth rate in Jakarta which is not matched by the increasing number of peaking tourists. The problem in this study is